CONCEPTUAL BASIS OF DEONTOLOGICAL TRAINING OF HEADS OF EDUCATIONAL ESTABLISHMENTS AT THE SECOND LEVEL OF HIGHER EDUCATION - Zadorozhna-Knyahnytska, Lenina (Continuing Professional Education: Theory and Practice, 2019)
The article presents the concept of deontological training of heads of educational establishments at the second level of higher education. The set of normative, legal and theoretical frameworks is defined, aspects of deontological training and relevant groups of professional requirements (legal, professional and technical, personal and professional) are grounded, its purpose and objectives in the context of selected aspects are formulated. The socio-cultural concept allowed to prove the need to develop the conception of deontological training of heads of educational establishments within the descriptive, normative and constructive approaches. Methodological principles of designing of the content of deontological training are taken under consideration. It is mentioned that the professional training of such a specialist is carried out in the context of the paradigmatic synthesis, which is a stable and harmonious combination of humanistic, culturological, anthropological and humanitarian educational paradigms that form an effective environment of the formation of deontological readiness. The characteristic of the system, personal, axiological, competence, active, synergistic, deontological approaches to the implementation of deontological training of future managers in education is given. Within the theoretical concept the system of definitions, output parameters, grades that are in the basis of the content and the structure and designing of its system is defined. The practical concept of the author’s conception that provides the control of the effectiveness of structural and component model of deontological training, identifying of appropriate educational conditions, criteria and outcome indicators are revealed.